2013
DOI: 10.1001/jamafacial.2013.25
|View full text |Cite
|
Sign up to set email alerts
|

Full-Thickness Skin Graft Overlying a Separately Harvested Auricular Cartilage Graft for Nasal Alar Reconstruction

Abstract: To evaluate the aesthetic and functional outcomes of a full-thickness skin graft and a separately harvested auricular cartilage graft for nasal alar defects created by Mohs micrographic surgery.Design: Twenty patients with deep Mohs micrographic surgery defects of the nasal ala who underwent reconstruction with a full-thickness skin graft and an auricular cartilage graft were prospectively studied at a single tertiary care institution between 2010 and 2011 in a nonrandomized, nonblinded study. An ordinal 5-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…They found that a full-thickness skin graft and a separately harvested auricular cartilage graft were valuable and reliable tools for reconstructing deep nasal alar defects that require support to prevent alar retraction or collapse. 25 As every surgeon group in our study (chief, consultants, senior residents, and assistant doctors) has almost the same mean score, we can state that in our population there was no correlation between experience of the surgeon and the operative result.…”
Section: Discussionmentioning
confidence: 52%
“…They found that a full-thickness skin graft and a separately harvested auricular cartilage graft were valuable and reliable tools for reconstructing deep nasal alar defects that require support to prevent alar retraction or collapse. 25 As every surgeon group in our study (chief, consultants, senior residents, and assistant doctors) has almost the same mean score, we can state that in our population there was no correlation between experience of the surgeon and the operative result.…”
Section: Discussionmentioning
confidence: 52%
“…In a recent prospective study, the aesthetic outcome of 20 cases in which a full‐thickness skin graft and a separately harvested auricular cartilage were used for nasal ala reconstruction was assessed . Good‐to‐excellent outcomes were present when assessed by three surgeons independently.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Along the alar region, this challenge derives from the contour of the cartilage and the long free margin of the inferior rim, which can become misshapen under the forces of wound contracture. 4,8,19 Even the lateral soft tissue can fall victim to these stresses and, without adequate structural support, can lead to internal nasal valve collapse. 8,18 This outcome underscores the need to evaluate not only the defect location and size but also the extent of tissue elevation required for reconstruction.…”
Section: Discussionmentioning
confidence: 99%